2023
DOI: 10.1080/01916122.2023.2179679
|View full text |Cite
|
Sign up to set email alerts
|

Melissopalynological investigations of seasonal honey samples from the Greater Kruger National Park, Savanna biome of South Africa

Abstract: In melissopalynological studies, the investigation of pollen composition in honey samples reveals the geographical and botanical origin of the samples and links them to the regional climatic conditions. Honeybees (Apis mellifera), collect pollen and nectar for their nutritional requirements based on the seasonal availability of surrounding flora. In this study, pollen content in honey was temporarily investigated for seasonal differences of the bee foraged plants. A melissopalynological investigation was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…New research in the field of melissopalynology has revealed how pollen grains stored in the bees' honey, can be used as an indicator for bee foraging behaviour. This technique, when combined with vegetation surveys, can therefore be used to identify the diversity of plants available to bees within a given area, as well as the distances that bees are willing to travel to forage [75], and could become a valuable tool to assess the general health and biodiversity objectives of the corridor regions. Thus, strategic use of beehive fences at a local scale would not only offer a second barrier next to unpalatable crops, but they would also function as alternative income streams-the bees would pollinate the produce and could be strategically used as biodiversity indicators.…”
Section: Discussionmentioning
confidence: 99%
“…New research in the field of melissopalynology has revealed how pollen grains stored in the bees' honey, can be used as an indicator for bee foraging behaviour. This technique, when combined with vegetation surveys, can therefore be used to identify the diversity of plants available to bees within a given area, as well as the distances that bees are willing to travel to forage [75], and could become a valuable tool to assess the general health and biodiversity objectives of the corridor regions. Thus, strategic use of beehive fences at a local scale would not only offer a second barrier next to unpalatable crops, but they would also function as alternative income streams-the bees would pollinate the produce and could be strategically used as biodiversity indicators.…”
Section: Discussionmentioning
confidence: 99%